ANALISIS PENILAIAN KEBUTUHAN PEMBELAJARAN DI SEKOLAH MENENGAH ATAS - Aulia, Ainun Meryna; Safitri, Ika (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
One of the strategic steps to improve the quality of education and the effectiveness of the teaching and learning process in senior secondary schools (SMA) is learning needs assessment analysis. This article discusses the importance of needs analysis, the techniques used, results, and application in learning in high schools. Surveys, interviews, and observations are commonly used techniques to identify student characteristics, suitability of materials, and required learning resources. The results of the analysis show that the curriculum and teaching methods must be adjusted to better suit students' interests and learning styles. Changing curricula, providing teacher training, and providing a variety of learning resources are all steps that must be taken to implement these findings. So, learning needs analysis not only increases students' desires but also improves their overall academic performance. This means a better and more supportive learning environment.